Translation and validation of the Chinese version of the Japan Frailty Scale - Wan, Dong-Ping; Wang, Rui; Wei, Jie; Zan, Qiang; Shang, Lei; Ma, Jianbing; Yao, Shuxin; Xu, Chao (Frontiers in Medicine, 2023)
Purpose: Frailty is a difficult-to-measure condition that is susceptible to adverse outcomes. The Japan Frailty Scale (JFS) is a tool for assessing frailty status in older adults. This study aimed to translate and culturally adapt the JFS into a Chinese version (JFS-C).The study included 160 older adults as participants. Internal consistency was assessed using Cronbach's alpha, and test-retest reliability was conducted using the intraclass correlation coefficient (ICC). Convergent validity was evaluated by assessing the correlation between JFS-C and the Barthel Index, the Frail scale, and the 36-item Short-Form Health Survey (SF-36). Criterion validity was assessed by comparing JFS-C scores with the Frail scale.Results: JFS-C demonstrated adequate internal consistency (Cronbach's alphas = 0.711) and excellent test-retest reliability over a 7 to 10-day interval (ICC = 0.949). Correlation analysis showed a strong positive correlation between JFS-C and the Frail scale (r = 0.786, P < 0.001), a moderate negative correlation with the Barthel Index (r = -0.598, P < 0.001), and moderate correlations with various subscales of SF-36 (r = -0.574 to -0.661). However, no significant correlations were found between JFS-C and SF-36 mental health (r = -0.363, p < 0.001) or role emotional (r = -0.350, p < 0.001). Based on the reference standard of the Frail scale phenotype (score ≥ 2), the cutoff value for JFS-C was determined to be 3.Conclusions: JFS-C demonstrates good reliability and validity in assessing frailty among the older population in China.